L1 Use in L2: Should We Omit It? Reexamining the L2- Only Policy in Foreign Language Classroom - Anisatul Maghfiroh; Ahmad Choirul Anwar (Universitas Teuku Umar, 2019)
The use of L2-only policy in foreign language classroom has been debated in academia. Questions around the debate revolve around; will it really be very effective and fruitful as well as comfortable for both the students and teachers of foreign language classes to use only L2 and completely omit L1 in their classroom activities? If not, how much should we limit the use of L1 in order to create a comprehensive language acquisition in class? The objective of this paper is to map the discussion about some supporting and opposing arguments on L2-only policy in foreign language classroom. Studies suggest that even though there are some opinions that L1 equals to comfort zone, we argue that there will not be any advantages to put the students in their anxiety when learning new language. Instead, students will feel uneasy and will result in their lack of motivation.